2020
DOI: 10.3390/ma13133011
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Cell Culture Devices: Assessment and Prevention of the Cytotoxicity of Photopolymers for Stereolithography

Abstract: 3D printing is increasingly important for the rapid prototyping of advanced and tailor-made cell culture devices. In this context, stereolithography represents a method for the rapid generation of prototypes from photocurable polymers. However, the biocompatibility of commercially available photopolymers is largely unknown. Therefore, we evaluated the cytotoxicity of six polymers, two of them certified as biocompatible according to ISO 10993-5:2009, and we evaluated, if coating with Parylene, an inert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…The aforementioned testing, encompassing systemic injection (acute systemic toxicity), intracutaneous and implantation tests, concluded classification of the material as USP IV according to the United States Pharmacopeia and National Formulary (USP-NF) [ 25 ]. These findings coincide with other reports found in the literature [ 26 , 27 ]. The verified biocompatibility of the polymer is a prerequisite for the potential clinical applicability of the proposed MN patch.…”
Section: Resultssupporting
confidence: 93%
“…The aforementioned testing, encompassing systemic injection (acute systemic toxicity), intracutaneous and implantation tests, concluded classification of the material as USP IV according to the United States Pharmacopeia and National Formulary (USP-NF) [ 25 ]. These findings coincide with other reports found in the literature [ 26 , 27 ]. The verified biocompatibility of the polymer is a prerequisite for the potential clinical applicability of the proposed MN patch.…”
Section: Resultssupporting
confidence: 93%
“…While PDMS is biocompatible for cell culture, there is no available data regarding commercial 3D-printing resins cytotoxicity (despite some of them being classified as biocompatible). Indeed, it was shown that different photopolymers for 3D-printing have different cytotoxic effects on cells, ranging from very low to high [56]. Applications such as the MOC in which cells are exposed to culture medium for days, are more exposed to leachable cytotoxic effects than devices that are used for short-term applications.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that this DLP 3D printing fabrication method will enable the polymeric SlipChips, and in particular the movable port technology, to become accessible to other labs, by greatly simplifying the fabrication steps, materials, and time. Continued advances in biocompatibility of DLP resins [ 47 , 48 , 49 ] may eventually enable longer-term culture on the 3D printed chip, which was a limitation here. Furthermore, while the current device used binder clips, visual alignment, and manual slipping, 3D printing may enable rapid iteration in the future of other clamping methods and pre-programmed integration with manipulators.…”
Section: Discussionmentioning
confidence: 99%